Kerinduan (Akan) Kebijaksanaan Abadi - Prasetyantha, Y.B. (Jurnal Orientasi Baru, 2007)
The longing for Christ as Wisdom marks the most singular trait of the spiritual journey and the work of St. Louis-Marie de Montfort. That is clearly reflected in The Love of Etemal Wisdom, a work of Montfort's youth, dating from the first years of his priestly ministry. In this christological masterpiece, young Montfort meditates on the paradoxical mystery of the crucified Christ, the incarnate Wisdom of God. This article is an attempt to discover Montfort's discourse on Wisdom and its relevance to the Indonesian context, especially in dealing with poverty and religious plurality.